CAREER PREFERENCE ASSESSMENT OF AGRICULTURAL STUDENTS USING PAIRED COMPARISION METHOD - MRIDULA N*; SAKEER HUSAIN A (The Journal of Research ANGRAU, 2020)
The study was conducted among 300 agricultural graduates of Kerala state to find their most preferred job among the five options selected by the judges, viz., Assistant Professor, Agricultural Officer, Banker, Farmer and Agripreneur. Paired comparision method, established by L.L. Thurston, based on the law of comparative judgement was used for the study. From the scale values obtained it was found that the most preferred job was that of an agricultural officer and least preferred job was of that of a farmer. The reluctance of agricultural students to take up farming and agripreneurship calls for attention to the fact that they should be given proper orientation regarding the emerging opportunities in these arenas during their undergraduate education periods. This is essential to channelize the skilled and knowledgeable manpower into the farming and agribusiness sector and to contribute to the sustainable entrepreneurship scenario of this agricultural country.